Neonatal Wnt-dependent Lgr5 positive stem cells are essential for uterine gland development - Ryo Seishima (Nature Portfolio, 2019)
Uterine gland development is essential for successful embryo implantation, decidua formation and placental development. Here the authors demonstrate that neonatal Wnt-dependent Lgr5 expressing stem/progenitor cells at the tips of developing glands are indispensable for uterine gland development.